Penerapan Metode Analytical Hierarchy Process (Ahp) Dalam Pemilihan Supplier Bahan Baku (Studi Kasus: Pt Berkah Jaya Mandiri Kabupaten Bandung) - Yuliyanti, Iis; Somadi, Somadi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The frozen food industry has experienced rapid growth due to changes in consumer consumption patterns that prioritize practicality and time efficiency. PT Berkah Jaya Mandiri, a company engaged in processing chicken bones into Mechanically Deboned Meat (MDM), faces challenges in raw material supplier selection, which has traditionally been dominated by the lowest-price consideration. This condition has resulted in unstable raw material quality, delivery delays, and production fluctuations that disrupt the company’s operational efficiency. This study aims to identify relevant supplier selection criteria and determine the optimal priority supplier using the Analytical Hierarchy Process (AHP) method. The results indicate that quality is the most influential criterion with a weight of 0.403 (40.3%), followed by delivery punctuality 0.267 (26.7%), price 0.187 (18.7%), supply capacity 0.086 (8.6%), and service 0.057 (5.7%), with a Consistency Ratio (CR) of 0.06. Based on the global priority values, CV. Andala ranks as the top supplier with a score of 0.284 (28.4%), followed by CV. Herlangga (0.247), CV. Sentra Protein (0.191), CV. Muzaky (0.156), and CV. Azka Boiler (0.122). The AHP method is proven to produce objective, systematic, and data-driven supplier selection decisions.